More than walking and cycling: What is 'active travel'?. (September 2022) - Cook, Simon; Stevenson, Lorna; Aldred, Rachel; Kendall, Matt; Cohen, Tom
Abstract: Where has the concept of 'active travel' come from and where is it taking us? In this paper, we explore these questions, firstly, through a systematic review that summarises the growth of active travel research over the last 15 years. This suggests a tendency to equate or reduce active travel to simply walking and cycling. We then move on to explore what expanding this definition to include all "travel in which the sustained physical exertion of the traveller directly contributes to their motion" would mean for active travel research and the modes it studies. To do this, we provide a thematic review of the limited transport literature into wider active travel modes (such as running, kick scooting, skateboarding and wheelchair use). The thematic review discusses six threads (emergence, fun, inclusivity, safety, regulation, and design) that explore what is known about these wider active modes and how transport research characterises them. We conclude with a discussion of the likely implications of expanding the definition of active travel more widely for policy, practice and transport-related research. While not risk-free, we argue that embracing an expanded notion of active travel has much to offer and it should be approached more broadly within transport studies than it is. Graphical abstract: Image 1 Highlights: Re-examines the concept of active travel, offering a more inclusive definition. Seeks to expand active travel to modes beyond just walking and cycling. Systematically reviews the growth of active travel. Thematically reviews transport research into wider active travel modes. Debates the policy, practice and research implications of expanding active travel.